THE RELIABILITY OF DETERMINING THE SHORT CIRCUIT ZONE OF THE LINES OF 6–35 kV - F. А. Romaniuk; E. V. Buloichyk; O. A. Huryanchyk; V. S. Kachenya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
A method of increasing the reliability of determining the zone of short-circuit at the current step protection of the lines of 6–35 kV with unilateral power, aimed at improvement of their technical perfection, is presented in the paper. Having taken the relative simpleness of the current protection into account the authors consider the unilateral remote method of accounting the parameters of the emergency mode and the type of fault to be the most suitable for the implementation of the algorithm of its functioning as compared with the existing methods of fault location. The major factors affecting the accuracy of determining the short circuit zone based on the remote method are noted. With the use of the method of computational experiment the influence of the load currents and contact resistances of various levels on the magnitude and character of changes of errors of determination of the calculated distance of the point of fault from the protection installation location taking into account the errors of measuring transformers. It is demonstrated that in many cases of arc short circuit in a loaded line in order to define the zone of short-circuit with fair accuracy correction of the estimated distance to the fault as calculated by the parameters of the damaged loop (loops) is required. According to the results of numerical experiments corrective expressions on the basis of two relative asymmetry currents determined by the current values of the differences of the phase currents of the line for detecting a type of a short circuit have been obtained. The assessment of the efficiency of the proposed method has been performed. It is shown that the application of the proposed correction method makes it possible to increase the accuracy of fault zone detection. The dynamic properties of the proposed method applied to different modes of the line functioning have been studied. It is determined that in the worst case the definition of the fault zone for a maximum duration of 26 μsec is provided.